2021
DOI: 10.24349/acarologia/20214441
|View full text |Cite
|
Sign up to set email alerts
|

Phytoseiid mites of the French Guiana (Acari: Mesostigmata)

Abstract: Only little information is available of the diversity of Phytoseiidae in French Guiana. So far, only one mite species of the family Phytoseiidae have been actually recorded, Amblydromalus limonicus. We report in this paper the results of a small survey conducted at the end of October / Mid November 2001 in French Guiana, during which 5 species have been newly recorded, one being re-described in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This species is cosmopolitan and considered a polyphagous predatory mite. It has been reported on a wide range of plants, particularly in vineyards (Kreiter et al 2000) and on fruit trees like in apple orchards as reported by Tixier et al (2013). In addition, it feeds on many species of mites, such as Aculops lycopersici (Tryon) (Eriophyidae) responsible for tomato russet, key pests of ornamental coniferous plants, i.e., Oligonychus ununguis (Jacobi) and Pentamerismus taxi (Haller), and pollen of Pinus sylvestris L. (Pinaceae) (Lara et al 2012; Puchalska et al 2021.…”
Section: Subtribe Amblyseiina Mumamentioning
confidence: 99%
“…This species is cosmopolitan and considered a polyphagous predatory mite. It has been reported on a wide range of plants, particularly in vineyards (Kreiter et al 2000) and on fruit trees like in apple orchards as reported by Tixier et al (2013). In addition, it feeds on many species of mites, such as Aculops lycopersici (Tryon) (Eriophyidae) responsible for tomato russet, key pests of ornamental coniferous plants, i.e., Oligonychus ununguis (Jacobi) and Pentamerismus taxi (Haller), and pollen of Pinus sylvestris L. (Pinaceae) (Lara et al 2012; Puchalska et al 2021.…”
Section: Subtribe Amblyseiina Mumamentioning
confidence: 99%
“…Distribution: Turkey, Iran, Algeria, Tunisia, Russia, Moldova, Italy, Caucasus Region, Armenia, Lebanon, Azerbaijan, Georgia, Greece, Croatia, Israel and Kazakhstan (Kreiter et al 2000, Moraes et al 1986, Rahmani et al 2010. In Turkey, Ankara, Amasya, Burdur, Bursa, Edirne, Erzurum, Gümüşhane, İçel, Isparta, İstanbul, Adapazarı, Amasya, İzmir, Kars, Kastamonu, Konya, Muğla, Nevşehir, Niğde, Tekirdağ, Tokat and Zonguldak (Akçakoyunluoğlu 2017, Bayram and Çobanoğlu 2007, Çobanoğlu 1989, 2004, Faraji et al 2011, Kumral 2005, Madanlar 1992, Swirski and Amitai 1982, Şekeroğlu 1984.…”
Section: Beneficial Mites Determined In Hevsel Gardensmentioning
confidence: 99%